Avaliação da substituição parcial de cimento Portland por cinza de queima de biomassa no desempenho de argamassas - Jasper, Catarina Marchi (2024)
The present work aims to evaluate the feasibility of using ashes from biomass combustion as a partial substitute for Portland cement in mortar compositions, assessing the changes in the fresh and hardened states. The study involves a comparison between a reference mortar made of Portland cement (CEM I 42.5) with a mix ratio of 1:3 and a water/binder (W/B) ratio of 0.6, and mortars with partial substitution of cement mass by ashes at substitution rates of 5, 10, 15, 20, and 25%, maintaining the W/B ratio constant. In the fresh state, the workability of the mortars was evaluated through the flow table test, density, and air content. In the hardened state, compressive and flexural tensile strengths, density and open porosity were assessed. It was found that the variation in properties, both in the fresh and hardened states, tends to be inversely proportional to the increase in the percentage of ash incorporation.